El paradigma constitucional del proceso civil. Bases teóricas - Delgado Suárez, Christian (Pontificia Universidad Católica del Perú, 2024)
This essay offers a feasible and verifiable theoretical basis for affirming what is called the fourth procedural paradigm, corresponding to the constitutional perspective of the civil procedure or the constitutionalization of it, as an overcoming of its previous classical and instrumentalist stages. To this end, through the interdisciplinary method, the research uses constitutional law, legal interpretation and procedural law to reshape the theoretical bases of the civil process and give it a constitutionalized value through the recognition of fundamental procedural rights as directly applicable norms containing optimization mandates. If it is a question of constitutionalizing the civil procedure, the essay, then, does not only seek the safe passage through the account of the so-called procedural guarantees. On the contrary, the functional or utility method applied to the same imposes that the contribution is to recognize the judge of the Constitutional State the duty of judicial protection even of the same fundamental procedural rights in the face of the defect or absence of rules that should implement and densify the principle of effective jurisdictional protection. This will make it possible to deconstruct and reconstruct concepts such as the fundamental right to effective judicial protection and the right of action, removing from them the slogan of mere guarantees that allow access to jurisdiction, to give them the character of optimization mandates directly executed by judges. It is, then, about the protection of the procedure, within the procedure, by the judge.

El presente ensayo ofrece una base teórica posible y verificable para afirmar lo que se denomina como el cuarto paradigma procesal, correspondiente a la perspectiva constitucional del proceso civil o a la constitucionalización del proceso civil, como superación de sus anteriores etapas clásica e instrumentalista. Para ello, a través del método interdisciplinario, la investigación se vale del derecho constitucional, de la interpretación jurídica y del derecho procesal para remodelar las bases teóricas del proceso civil y otorgarle un valor constitucionalizado a través del reconocimiento de los derechos fundamentales procesales como normas de directa aplicación conteniendo mandatos de optimización. Si de constitucionalizar el proceso civil se trata, el ensayo, entonces, no solo busca el tránsito seguro por el recuento de las así llamadas garantías procesales. Por el contrario, el método funcional o de utilidad aplicado al mismo impone que el aporte pase por reconocerle al juez del Estado Constitucional el deber de tutela judicial incluso de los mismos derechos procesales fundamentales frente al defecto o ausencia de reglas que debiesen implementar y densificar el principio de tutela jurisdiccional efectiva. Con esto se permitirá deconstruir y reconstruir conceptos como el derecho fundamental a la tutela jurisdiccional efectiva y el derecho de acción, retirándoles el slogan de meras garantías que permiten el acceso a la jurisdicción, para endosarles el carácter de mandatos de optimización directamente ejecutados por los jueces. Se trata, entonces, de la tutela del proceso, en el proceso, por parte del juez.
The constitutional paradigm of civil procedure. Theoretical bases
Keywords: Effective jurisdictional protection; Right of action; Direct effectiveness; Fundamental rights; Constitutional paradigm of the process; Civil Procedure; Peru; Tutela jurisdiccional efectiva; Derecho de acción; Eficacia directa; Derechos fundamentales; Paradigma constitucional del proceso; Derecho Procesal Civil; Perú; https://purl.org/pe-repo/ocde/ford#5.05.00